PERCEPTIONS OF EFL LEARNERS ON THE APPLICATION OF READING ALOUD TECHNIQUE IN LEARNING PRONUNCIATION - Ichsanul Faraby; Abdul Kamaruddin (e-Journal of ELTS (English Language Teaching Society), 2021)
The objective of this research was to find out whether or not the use of Sequence Pictures Technique can improve the ninth grade students’ skill in writing procedure text. The researcher applied a quasi-experimental research design. The population of this research was the ninth grade students of SMP Negeri 14 Palu which consisted of 119 students. The sample of this research was 30 students of class IX Ahmad Yani as the experimental class. Meanwhile, 29 students of class IX Cut Nyak Dien categorized as the control class. The sample was selected by using cluster random sampling technique. The technique of data collection was test. The test included pre-test and post-test, with the mean score of 56.11 for experimental class, and 71.67 for control class on pre-test. While on post-test, the results were 73.33 for experimental class and 77.22 for control class. By applying 0.05 level of significance and 28 degree of freedom (df), as can be seen that the value of t-counted was (3.58) and t-table was (1.701). The t-counted value was higher than t-table value, which meant that the research hypothesis was accepted. This study suggests that the use of Sequence Pictures technique can improve students’ writing skill in procedure text.